Memória como acontecimento da cultura: uma análise do museu da pessoa a partir de Bakhtin e de Lotman - Lima, Caroline Aparecida de (2022)
The aim of this master's thesis is to propose a theoretical-epistemological reflection on a virtual museum the Museum of the Person, that houses testimonies and narratives of the historical subjects themselves, as memory events. Based on this general objective, based on the Bakhtinian theoretical framework in dialogue with the Lotmanian framework, the specific objectives are: a) to analyze the interrelations between memory and culture processes, which (re)present the constant coming to be of the subjects that coexist; b) to understand how signs are a means of (re)constructing the memory of these subjects as unique and alteritary events (since, in our conception, questions about memory necessarily go through dialogues with semiotic approaches) and c) to reflect on the volitive-emotional tone as a process that participates in the constitution of these memories. Thus, on the processes that involve the constitution of subjects through memory, we establish the process by which from the talk of one another reverberates in time/space in contact with others who attend the memorialistic statements and are affected, (re)meaning memory, so the condition of evaluation occurs through semiotic means, which deals with social interactions, that understands memory as an active storehouse for/from culture.